Early Termination and Pipelining for Hardware Implementation of Fast H.264 Intraprediction Targeting Mobile HD Applications. (9th October 2008) - Jung Jung, Jin-Su Jin-Su; Jin Jin, Genhua Genhua; Lee Lee, Hyuk-Jae Hyuk-Jae
Abstract : H.264/AVC adopts aggressive compression algorithms at the cost of increased computational complexity. To speed up the H.264/AVC intraframe coding, this paper proposes two novel techniques: early termination and pipelined execution. In P slices, intra4 × 4 and16 × 16 predictions are early terminated with the threshold determined by the cost of motion estimation. In I slices, intra4 × 4 prediction is early terminated with the threshold derived from intra16 × 16 prediction. The threshold function is chosen as a monotonically decreasing linear function with its optimal coefficients determined by experiments. For the pipelined execution of4 × 4 intrapredictions, the processing order of4 × 4 blocks is changed to reduce the dependencies between consecutively processed blocks. In I slices, computation for4 × 4 intraprediction is reduced by 19 percent with the proposed early termination. In P slices, computations for4 × 4 and16 × 16 intrapredictions are reduced by more than 81 and 91 percents, respectively. The pipelined execution reduces the computation time by 41 percent. In spite of the speed-up by the proposed methods, degradation in rate-distortion performance is negligible. The proposed pipelined execution is integrated with other H.264/AVC hardware accelerators and fabricated as an SoC using Dongbu 0.13 μ m technology.